2021
DOI: 10.1089/neu.2020.7229
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan 4 Reduces Neuroinflammation and Protects the Blood–Brain Barrier after Traumatic Brain Injury

Abstract: Neuroinflammation and dysfunction of the blood-brain barrier (BBB) are two prominent mechanisms of secondary injury in neurotrauma. It has been suggested that Toll-like receptors (TLRs) play important roles in initiating and propagating neuroinflammation resulting from traumatic brain injury (TBI), but potential beneficial effects of targeting these receptors in TBI have not been broadly studied. Here, we investigated the effect of targeting TLRs with proteoglycan 4 (PRG4) on post-traumatic neuroinflammation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…rhPRG4 was also shown to reduce cytokine and chemokine secretions from immortalized corneal epithelial cells at 300μg/mL in vitro and inflammation in an experimental dry eye disease model ( 61 ). rhPRG4 reduced neuroinflammation and influx of monocytes in a rat model of traumatic brain injury, mediated by its regulation of the ERK1/2 pathway, downstream of CD44 and TLR2/4 engagements ( 62 ). Our current study extends the anti-inflammatory activity of rhPRG4 to controlling IL-1β secretion by PBMCs from patients with acute gout flares, where the efficacious rhPRG4 concentration was in the range of what was reported as efficacious in in vitro models of human synoviocytes, macrophages, endothelial and corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…rhPRG4 was also shown to reduce cytokine and chemokine secretions from immortalized corneal epithelial cells at 300μg/mL in vitro and inflammation in an experimental dry eye disease model ( 61 ). rhPRG4 reduced neuroinflammation and influx of monocytes in a rat model of traumatic brain injury, mediated by its regulation of the ERK1/2 pathway, downstream of CD44 and TLR2/4 engagements ( 62 ). Our current study extends the anti-inflammatory activity of rhPRG4 to controlling IL-1β secretion by PBMCs from patients with acute gout flares, where the efficacious rhPRG4 concentration was in the range of what was reported as efficacious in in vitro models of human synoviocytes, macrophages, endothelial and corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…To exert the anti-inflammatory effect, the agents or molecule may target certain type of immune cells to enhance their function, change the phenotypes, inhibit the secretion of pro-inflammatory factors, or enhance the secretion of anti-inflammatory factors (Table 2). There are several agents attenuate inflammation by inhibiting the accumulation and activation of immune cells, such as microglia, T cells, astrocytes, and monocytes (Prabhakara et al, 2018;Hummel et al, 2020;Bennett et al, 2021). More studies have focused on the process of shifting from M1 microglial phenotype to the M2.…”
Section: Anti-inflammation To Enhance the Microenvironmentmentioning
confidence: 99%
“…A study has demonstrated that P7C3-A20, a compound that stabilizes the cellular energy levels, could increase the expression of TJ proteins in different region of the brain, e.g., claudin-5 in the cortex and hippocampus, and zona occludens-1 in the cortex (Vázquez-Rosa et al, 2020). Other agents or drugs, such as proteoglycan 4, rhFGF21 (Bennett et al, 2021), sesamin (Liu et al, 2017), capsazepine (TRPV1 inhibitor) (Yang D. X. et al, 2019), glibenclamide (Xu et al, 2017), TIMP1 (Tang et al, 2020), and TIMP3 (Menge et al, 2012) also have the effect on the expression of TJ and AJ proteins, such as claudin 5, occludens-1, and ZO-1.…”
Section: Agents In Microenvironment Targeting Blood-brain Barriermentioning
confidence: 99%
“…It is well known that maintaining BBB integrity is crucial for homeostasis of the CNS. It is worth noting that the excessive neuroinflammatory responses may also damage the junctional complex of the BBB, leading to BBB dysfunction in a variety of inflammatory CNS diseases ( Chen et al, 2014a ; Bennett et al, 2021 ). Chen et al (2014a) showed that the overexpression of matrix metallopeptidase (MMP)-9 and vascular endothelial growth factor (VEGF) after SAH promoted the increase in BBB permeability, which was closely associated with both neuroinflammation and brain edema.…”
Section: Introductionmentioning
confidence: 99%